Model characteristics of olympic sport organisations in Slovenia - Bednarik, Jakob (Kinesiologia Slovenica, 2000)
The study deals with the characteristics of Olympic-sports organisations in Slovenia and the main differences in relation to non-Olympic sports organisations dealing either with competitive or recreational sport. Two samples were obtained. The data on the employee structure comes from a sample of 366 sports organisations, representing about one sixth of all sports organisations, while the financial data mirrors incomes and expenditures of fifty-five sports. The organisations and sports were classified into Olympic, non-Olympic competitive sports and recreational sports ones. The cadre and financial structure and the differences were analysed with descriptive statistics, chi-square statistics and canonical discriminant analysis. Slovenian sports organisations are mainly managed voluntarily. Olympic sports organisations are situated mostly in cities, are smaller, have much higher incomes and expenditures and a relatively high level of professionalisation. Statistically significant differences were found between the three types of organisations in siye, seat, income and expenditure and cadre structure. The most discriminating variables were the number of voluntary technical staff, honorary administrative staff, voluntary medical staff and full-time instructors.
Keywords: analiza; olimpijske panoge; rekreativni šport; Slovenija; šport; športne organizacije; tekmovalni šport